2018
DOI: 10.1016/j.htct.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and cytogenetic profiles of patients with hematological malignancies and their relationship with aging

Abstract: BackgroundHematologic neoplasms are associated with mutations in hematopoietic cells and chromosomal abnormalities. During aging, about 2–3% of the elderly have chromosomal abnormalities arising from clonal mosaicism, the immune system is impaired and the bone marrow loses its ability to replace blood cells.ObjectiveTo describe the epidemiological and cytogenetic profile of hematological malignancies, highlighting the frequency of chromosomal alterations in these neoplasms associated with aging.MethodA retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“… 5 The paper by Alves et al presents very interesting data and discussion about the influence and mechanisms associated to frequency, gender, diagnosis and prognosis of onco-hematological diseases and aging. 1 Moreover, we can see the most frequent CA observed by the authors in a single Brazilian University Laboratory.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“… 5 The paper by Alves et al presents very interesting data and discussion about the influence and mechanisms associated to frequency, gender, diagnosis and prognosis of onco-hematological diseases and aging. 1 Moreover, we can see the most frequent CA observed by the authors in a single Brazilian University Laboratory.…”
mentioning
confidence: 81%
“…In a retrospective analysis of a large sample (746 patients) over 18 years of observation and including several types of onco-hematological diseases in patients of all ages, the authors investigated the influence of age on the frequency of CA. 1 The authors found a higher frequency of hematological malignancies among elderly patients, about 51%, followed by adult (38%) and young patients (about of 11%). The authors reported that “it is possible to conclude that failures in genomic mechanisms and hematopoiesis with aging lead to the formation of cells with the chromosomal alterations found in hematological malignancies”.…”
mentioning
confidence: 94%
“…Os tumores malignos podem ser divididos de acordo com sua origem. Assim, tumores que afetam as linhagens de células sanguíneas são conhecidos como tumores hematológicos (THs) e os tumores caracterizados por aglomeração de células neoplásicas, são os chamados de tumores sólidos (TSs) (Alves et al, 2018;INCA, 2020). Mesmo com diferentes origens, os tumores acarretam várias alterações no metabolismo, causando impactos na qualidade de vida do indivíduo (INCA, 2020).…”
Section: Introductionunclassified